2016
DOI: 10.1038/nature20157
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of super-assembly of respiratory complexes III and IV

Abstract: Respiratory chain complexes can super-assemble into quaternary structures called supercomplexes that optimize cellular metabolism. The interaction between complexes III (CIII) and IV (CIV) is modulated by supercomplex assembly factor 1 (SCAF1, also known as COX7A2L). The discovery of SCAF1 represented strong genetic evidence that supercomplexes exist in vivo. SCAF1 is present as a long isoform (113 amino acids) or a short isoform (111 amino acids) in different mouse strains. Only the long isoform can induce th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
199
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(222 citation statements)
references
References 19 publications
23
199
0
Order By: Relevance
“…These studies concluded that mice bearing the shortened form of the subunit have normal biogenesis, no related respiratory defects, and normal levels of complex IV-associated supercomplexes, although differences in levels of different supercomplex subtypes were observed. In support of the hypothesis that COX VIIaR is required for supercomplex assembly, however, another recent publication showed that the long form of COX7AR was required for interaction of complexes III and IV [194]. Here, it was shown that the individual supercomplexes employ different isoforms to achieve different stoichiometries.…”
Section: Isoforms Of Cytochrome C Oxidase Subunitsmentioning
confidence: 79%
“…These studies concluded that mice bearing the shortened form of the subunit have normal biogenesis, no related respiratory defects, and normal levels of complex IV-associated supercomplexes, although differences in levels of different supercomplex subtypes were observed. In support of the hypothesis that COX VIIaR is required for supercomplex assembly, however, another recent publication showed that the long form of COX7AR was required for interaction of complexes III and IV [194]. Here, it was shown that the individual supercomplexes employ different isoforms to achieve different stoichiometries.…”
Section: Isoforms Of Cytochrome C Oxidase Subunitsmentioning
confidence: 79%
“…These complexes have long been recognized as discrete entities embedded within the inner mitochondrial membrane, but they are also found as respiratory supercomplexes. The crystal structures of two functional supercomplexes (supercomplexes I and III) and the fully functional respirasome (consisting of complexes I, III, and IV) have recently been elucidated (12,32,55).…”
Section: The Dual Genetic Control Of Mitochondrial Functionmentioning
confidence: 99%
“…Two previously implicated SC stabilizing factors are COX7A2L and HIGD2. Although COX7A2L can exist within SC(I + III 2 +IV), it is now known to primarily facilitate the CIII–CIV interaction (Cogliati et al, 2016; Pérez-Pérez et al, 2016). Different isoforms of COX7A exist including COX7A1, COX7A2, and COX7A2L.…”
mentioning
confidence: 99%
“…Different isoforms of COX7A exist including COX7A1, COX7A2, and COX7A2L. The presence of COX7A2 isoform correlates primarily with unassociated monomeric CIV complex, whereas COX7A1-containing CIV species favor dimeric CIV complexes (Cogliati et al, 2016). Replacement of COX7A1 with COX7A2L (SCAFI) permits assembly of the CIII–CIV heterocomplex and SC formation in some tissues (Cogliati et al, 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation